2021
DOI: 10.3389/fimmu.2021.790051
|View full text |Cite
|
Sign up to set email alerts
|

Immune Thrombocytopenia Induced by Immune Checkpoint Inhibitrs in Lung Cancer: Case Report and Literature Review

Abstract: Immune checkpoint inhibitors (ICIs), including antibodies targeting programmed cell death protein-1 (PD-1) and programmed cell death ligand-1 (PD-L1), are being extensively used on advanced human malignancies therapy. The treatment with ICIs have acquired durable tumor inhibition and changed the treatment landscape in lung cancer. Immune-related adverse events including pneumonitis and thyroiditis have been well described, but less frequent events, such as ICIs-induced thrombocytopenia, are now emerging and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Previous studies have shown that the change in the frequency of T cells, particularly for Tregs, is associated with the pathogenesis of irAEs ( 23 , 35 ). Recent studies have noted that high levels of pro-inflammatory cytokines may contribute to the pathogenesis of irAEs ( 18 , 26 , 27 ). In this study, we found that combination of CAIA and ICI, but not their alone, caused significantly higher frequency of TNF-α secreting CD4 + and CD8 + T cells and higher percentages of effector memory T cells, but not IFN-γ, IL-4, and IL-17 secreting T cells and Tregs, in the circulation and peripheral lymph organs as well as in the lungs of humanized mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the change in the frequency of T cells, particularly for Tregs, is associated with the pathogenesis of irAEs ( 23 , 35 ). Recent studies have noted that high levels of pro-inflammatory cytokines may contribute to the pathogenesis of irAEs ( 18 , 26 , 27 ). In this study, we found that combination of CAIA and ICI, but not their alone, caused significantly higher frequency of TNF-α secreting CD4 + and CD8 + T cells and higher percentages of effector memory T cells, but not IFN-γ, IL-4, and IL-17 secreting T cells and Tregs, in the circulation and peripheral lymph organs as well as in the lungs of humanized mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many pro-inflammatory effectors and memory T cells infiltrate the targeted tissues and organs ( 22 24 ). Recently, some investigations have reported that high levels of pro-inflammatory IL-6, IL-17 and GM-CSF secretion may contribute to the onset of irAEs ( 25 27 ). However, what types of effector T cells are and how they mediate the onset of irAEs have not been clarified, particularly for the ICI-related arthritis and pneumonitis in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, large doses of methylprednisolone, immunoglobulin and rituximab, intermittent platelet transfusion, thrombopoietin, and hemoglobinogen being administered to the patient, and his conditions did not improve. (17), and ICI induced thrombocytopenia in only one case of SCLC (7). Haem-irAEs have not only been poorly understood and described but also lack consensus, whereas other common irAEs have well been characterized and managed.…”
Section: Discussion Among Physicians From the First Affiliated Hospit...mentioning
confidence: 99%
“…Isolated case reports and case series have presented the hematologic toxicities induced by ICIs, but the incidence, diagnosis, and biological mechanisms in such patients remain unclear ( 7 - 17 ). Previous reports have summarized immune thrombocytopenia induced by immune checkpoint inhibitors in lung cancer ( 17 ), and ICI induced thrombocytopenia in only one case of SCLC ( 7 ). Haem-irAEs have not only been poorly understood and described but also lack consensus, whereas other common irAEs have well been characterized and managed.…”
Section: Imdt Discussionmentioning
confidence: 99%
“…Tis situation is more complicated in liver cancer, which is the sixth most frequent cancer types and the fourth leading cause of cancer-related mortality globally because invasive therapeutic procedures [3], including hepatectomy, radiofrequency ablation, and biopsy, carry additional hemorrhage risk. Besides, for patients who receive systemic therapy, thrombocytopenia is not a rare event due to myelotoxicity or immunotherapy-related myelosuppression [4][5][6], resulting in chemotherapy dose reduction, prolonged interval between treatment cycles, or shifting to less-intensive regimens with the risk of a decreasing response rate and overall survival. Under such circumstances, thrombopoietic drugs, such as corticosteroids and recombinant human thrombopoietin, or platelet transfusion are often prescribed [7].…”
Section: Introductionmentioning
confidence: 99%